A business plan on opening a motorcycle assembly plant in Thailand for the assembly and sales of motorcycles in Thailand, that also complies with the ASEAN-Free Trade Agreement (AFTA) requirements - Sangaran, Judah Immanuel (2020)
Ducati Motor Holdings S.p.A. (Italy), Triumph Ltd (UK), Bayerische Motoren Werke AG (BMW German), Kawasaki Heavy Industries Ltd (Kawasaki Motorcycles Japan),and Harley Davidson Inc (USA) have an assembly plant in Thailand. By having their plants in Thailand, they enjoy the Thailand Board of Investment (BOI) tax exemption schemes, and also the Common Effective Preferential Tariff (CEPT) Scheme for AFTA (ASEAN-Free Trade Agreement).